2021
DOI: 10.1080/2162402x.2021.1929727
|View full text |Cite
|
Sign up to set email alerts
|

Effects of concomitant proton pump inhibitor use on immune checkpoint inhibitor efficacy among patients with advanced cancer

Abstract: Background: The present study aimed to evaluate the effects of concomitant proton pump inhibitor (PPI) use on immune checkpoint inhibitor (ICI) efficacy among advanced cancer patients. Methods and Materials: A systematic literature search of electronic database was performed to identify all potential reports. Then, meta-analyses were conducted to obtain pooled HRs with 95% CIs, which reveal the influence of PPI use on PFS and OS in patients receiving ICI treatment. Results: A total of 7 studies with 3,647 adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 44 publications
(83 reference statements)
2
32
0
Order By: Relevance
“…Therefore, in this study, we performed an up-to-date metaanalysis to clarify the correlation between PPI use and ICI efficacy in advanced solid cancers. During the preparation of our manuscript, it is worth mentioning that three similar studies have been published so far (36)(37)(38). Compared with them, on the one hand, our present work is an up-to-date analysis including more studies (n = 17 vs.…”
Section: Publication Bias and Sensitivity Analysismentioning
confidence: 89%
See 2 more Smart Citations
“…Therefore, in this study, we performed an up-to-date metaanalysis to clarify the correlation between PPI use and ICI efficacy in advanced solid cancers. During the preparation of our manuscript, it is worth mentioning that three similar studies have been published so far (36)(37)(38). Compared with them, on the one hand, our present work is an up-to-date analysis including more studies (n = 17 vs.…”
Section: Publication Bias and Sensitivity Analysismentioning
confidence: 89%
“…On the contrary, an updated investigation by Qin et al. in 2021 demonstrated a significant negative correlation of PPI use with OS and PFS in advanced cancer patients treated with ICIs ( 38 ). Despite the lack of supporting mechanism investigations, Qin et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a meta-analysis of seven studies (3647 cancer patients) was reported. The authors concluded that PPIs’ use had a detrimental effect on the efficacy of ICI: PPIs’ use increased the risk of death by 39% and the risk of progression by 28% [ 63 ].…”
Section: Ppis and Oncologic Treatment Efficacymentioning
confidence: 99%
“…Finally, other medications (e.g. antibiotics [82], proton‐pump inhibitors [83]) or dietary choices (e.g. high‐fibre intake [84]) may impact ICI efficacy (negatively or positively, respectively) via influencing our gut microbiome – the composition and diversity of resident microbiota living in our gastrointestinal tract.…”
Section: Phenotypic and External Featuresmentioning
confidence: 99%